The effect of profit sharing and financing ceiling on non-performing financing islamic banks - Nasfi, Nasfi; Yunimar, Yunimar; Sabri, Sabri; Febrianti, Eka; Asnah, Asnah (Faculty of Economics and Business Mulawarman University, 2021)
The purpose of this research is to find out how the influence of profit sharing and financing ceilings on Non Performing Financing in Islamic Banking. The effect of the level of profit sharing on Non-Performing Financing, as well as the effect of the financing ceiling on Non-Performing Financing in Islamic Banking in the City of Bukittinggi. The population in this study, a number of 35 debtors of Islamic banks whose businesses are classified as micro, small and medium enterprises that trade in Bukittinggi City. Data collection is based on the census method, namely the number of respondents in the population is the same as the sample. The analysis technique used is multiple linear regression. The variables in this study use the independent variables, namely the level of profit sharing (X1) and the financing ceiling (X2) while Non-Performing Financing (Y) is the dependent variable. The results of the study obtained the equation Y = 0.315 + 0.520X1 + 0.867X2, the significance value of the profit-sharing rate variable (X1) is 0.016 and the financing ceiling (X2) is 0.000 which means that there is a significant and positive effect on the profit-sharing rate (X1) on non-performing financing (Y) of Islamic banking, traders in Bukittinggi have a significant and positive influence on the financing ceiling (X2) on non-performing financing of Islamic banking in Bukittinggi City.